2022
DOI: 10.3390/photonics9120906
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Antireflection Coatings in Solar Cells

Abstract: The antireflection coating (ARC) suppresses surface light loss and thus improves the power conversion efficiency (PCE) of solar cells, which is its essential function. This paper reviews the latest applications of antireflection optical thin films in different types of solar cells and summarizes the experimental data. Basic optical theories of designing antireflection coatings, commonly used antireflection materials, and their classic combinations are introduced. Since single and double antireflection coatings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…To reduce reflection for solar cells and photodiodes, antireflection coatings (ARCs) [52][53][54] and surface texturing techniques [55][56][57][58][59][60][61] are designed. By carefully engineering the refractive index of the surface, the reflection can be minimized, allowing more light, particularly in the wavelength range of interest, to pass into the semiconductor material and be absorbed, resulting in higher device performance and new applications.…”
Section: Reduced Light Transmission Into Solar Cells and Photodiodesmentioning
confidence: 99%
“…To reduce reflection for solar cells and photodiodes, antireflection coatings (ARCs) [52][53][54] and surface texturing techniques [55][56][57][58][59][60][61] are designed. By carefully engineering the refractive index of the surface, the reflection can be minimized, allowing more light, particularly in the wavelength range of interest, to pass into the semiconductor material and be absorbed, resulting in higher device performance and new applications.…”
Section: Reduced Light Transmission Into Solar Cells and Photodiodesmentioning
confidence: 99%
“…Currently, multilayer composite thin-film coating is the most common approach to achieving AR. 10,11 However, the stability of the multilayer structures may be insufficient for hightemperature applications. With the development of photonics technology, interfaces can be designed with periodic subwavelength-scale structures, such as pillars, holes, pyramids, and cones.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, multilayer composite thin-film coating is the most common approach to achieving AR. , However, the stability of the multilayer structures may be insufficient for high-temperature applications. With the development of photonics technology, interfaces can be designed with periodic subwavelength-scale structures, such as pillars, holes, pyramids, and cones. The refractive index on both sides of the interface can gradually change using relief structures, avoiding light loss or reflection caused by abrupt refractive index changes without increasing the influence of diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The existing research on ARL is divided into two main categories, namely, membrane structure and micronano-optical structure [11,12]. Wang et al theoretically and experimentally concluded that the experimental porous SiO 2 and MgF 2 double-layer anti-reflection can improve the short-circuit current density of siliconbased stacked cells, and the ARL has good anti-reflection properties in the range of 400-1200 nm [13].…”
Section: Introductionmentioning
confidence: 99%